Moral Panic and Islamic Comic Preaching on Social Media: Study of @Iqomic on Instagram - Azhar, Azhar; Sahfutra, Suryo Adi (IAIN Ponorogo, 2023)
The Instagram account @Iqomic (Islamic Quotes and Comics) has popularized preaching content about Islamic comics through social media. Islamic comics initiated by comic artists are a phenomenon. Iqomic was formed in a network of comic artist groups or communities consisting of social media content creators, professional and amateur comic artists. This article reviews the @Iqomic account on social media, especially the Instagram application. Iqomic is an Islamic comic preaching account whose mission is to spread goodness and convey Islam's blessings to all. In analyzing the Islamic comic da'wah movement carried out by the Icomic community, the author uses moral panic to explore how the Iqomic community spreads and mobilizes comic da'wah as an effort to fight negative discourse about Islam, such as anarchy, terrorism and radicalism in its environment. Islamic community itself. The author is of the opinion that, in response to the emergence of various negative discourses about Islam, Iqomic has succeeded in becoming a popular da'wah media by incorporating Islamic narratives into popular Islamic culture among teenagers and young adults, so that it has become one of the favorite platforms for sharing stories and being creative.